The Evaluation of Soteriology in Inclusivist Theology - Goktondi Pasaribu (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2023)
The theology of inclusivism is one of the three theological approaches in the study of religion. This approach was proposed by Alan Race in his discourse on the relationship between religions. Inclusivism holds a concept of salvation that combines or reconciles the concept of salvation from two other theological approaches, namely exclusivism and pluralism. Exclusivism takes a firm stance and asserts that salvation is only through Jesus as mentioned in the Scriptures. On the other hand, pluralism believes that all religions are valid, and none is superior to the other. Inclusivist theology brings both together by stating that salvation is only possible through Jesus Christ; thus, the requirement for belief is to believe in Jesus. However, other religions can also receive salvation because they have access to Jesus through general revelation. People who attain salvation without believing in Jesus but have access to him through general revelation are called anonymous Christians, namely, brothers at the very margins. This concept is highly demanded by many people, including Christians, as it is more reasonable and tolerant. How does this concept of inclusivity in salvation align with the biblical perspective? This research is a qualitative study that will examine the truth of the concept of inclusivism based on the exegesis of three verses, namely John 14:6, Acts 4:12, and 1 Timothy 2:15.